1996
DOI: 10.1210/endo.137.11.8895393
|View full text |Cite
|
Sign up to set email alerts
|

Persistent transgene expression in the hypothalamus following stereotaxic delivery of a recombinant adenovirus: suppression of the immune response with cyclosporin.

Abstract: Replication deficient, recombinant adenoviruses (Ads) have been used successfully to transfect several forebrain and brainstem nuclei, but have yet to be demonstrated as useful vectors for transgene delivery in the structurally diverse and highly vascularised nuclei of the hypothalamus. In the present study we have assessed the ability of an Ad expressing the lac-Z gene to transfect cells of the paraventricular nucleus (PVN) of the hypothalamus in vivo. We show that: (1) we can achieve stable expression of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(12 citation statements)
references
References 10 publications
2
10
0
Order By: Relevance
“…The comparisons were made between animals that had been injected with A-CREB and control adenoviral vectors, so that the transduction itself may be excluded from being responsible for the behavioral, Fos, pCREB, and plasticity impairments. Previous studies have also shown that adenoviral vectors elicit a negligible immune response when measured several weeks after injection at the titers used in the present study (Byrnes et al, 1995;Geddes et al, 1996;Gerdes et al, 2000). The behavioral effects clearly originate in the perirhinal cortex and/or Te2, because that is the region that was virally transduced and the region in which differential Fos and pCREB expression was disrupted.…”
Section: Discussionsupporting
confidence: 54%
“…The comparisons were made between animals that had been injected with A-CREB and control adenoviral vectors, so that the transduction itself may be excluded from being responsible for the behavioral, Fos, pCREB, and plasticity impairments. Previous studies have also shown that adenoviral vectors elicit a negligible immune response when measured several weeks after injection at the titers used in the present study (Byrnes et al, 1995;Geddes et al, 1996;Gerdes et al, 2000). The behavioral effects clearly originate in the perirhinal cortex and/or Te2, because that is the region that was virally transduced and the region in which differential Fos and pCREB expression was disrupted.…”
Section: Discussionsupporting
confidence: 54%
“…8 However, since these vectors also deliver large amounts of viral sequences they often cause host immune reactions and tissue damage, an affect which can be prevented by immunosuppressants including glucocorticoids. 12,13,16 The lack of any detectable inflammation in the adrenal following intra-adrenal injection of the adenoviral constructs suggests that in contrast to other tissues, the high levels of endogenous steroids in this tissue may have a protective effect preventing inflammatory responses. This makes the adrenal an immune privileged organ and an ideal candidate for gene therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Survival of the transgene delivered by adenoviruses can be limited by both the spontaneous elimination of the episomal viral DNA and the immune response to the viral antigens produced by transfected cells. While the immune response limits the value of the adenoviruses for gene delivery into peripheral tissues, this response is less intense in the brain and can be suppressed by cyclosporin (Geddes et al 1996). Geddes et al (1996 demonstrated that the lacZ gene introduced using adenoviruses into the paraventricular nucleus of the hypothalamus persisted for at least 2 months.…”
Section: Survival Of Transgenes Delivered By Adenoviral Vectorsmentioning
confidence: 99%